An Islamic perspective on food and nutrition and the relevancy of al-Ghazali’s spiritual view on modern practices - Ssuna, Salim (2020)
A Muslim way of feeling, thinking and acting must manifest his surrender to the Almighty Allah, with the main aim of attaining felicity in the life of this World and life in the Hereafter. Foods and nutrition are among the most important factors that to a greater extent influence the spirituality of an individual. The Quran and the Sunnah of the prophet (peace be upon him) placed more emphasis on this aspect as its neglect results into failure of an individual to full fill his obligation as a vicegerent which may lead to a life of punishment in the Hereafter. This study will critically analyse the Muslim practices on food and nutrition during modern times in comparison with al-Ghazali’s views on the effect of dietary practices on the spiritual aspect of a Muslim. The study uses an evaluative deductive methodology on the existing literature of the topic, culminating into synthesis of al-Ghazali view and its relevancy to contemporary Muslim times. It is observed that much as modern Muslims are in most cases aware of halal and haram concepts and the negative effects and influence of food and nutrition on their lives, they are still facing serious spiritual problems and challenges discernible in moral decadence which al-Ghazali ; a scholar of the 11th Century provided an insight solution.